Slab Planning Of A 5-Storey Apartment Building On Jalan Pemuda Semarang - Sumarman Sumarman (Riviera Publishing, 2025)
This research focuses on the design of a bidirectional reinforced concrete slab for a 5-storey apartment building located on Jalan Pemuda, Semarang, following SNI 1726:2019 standards. The objective is to compare the results of the direct design method (DDM) using Excel with ETABS v18 software, analyzing the accuracy of traditional methods in modern structural designs. The study employed a practical approach, incorporating various design parameters such as beam dimensions, span length, dead and live loads, and material strengths (f'c and fy). The results indicate that although there is a slight difference between the methods, they exhibit similar trends. The study found that increased load leads to higher moments, while larger beams and higher concrete strength reduce reinforcement requirements. However, discrepancies between the methods were observed due to rounding errors in the DDM. The research suggests refining moment calculation techniques and enhancing software tools for more accurate slab designs. The findings are essential for improving design accuracy in both academic and professional practice, particularly for earthquake-resistant structures.